Pengaruh Jenis Larutan Osmotik pada Invigorasi Benih Kakao (Theobroma cacao L.) dengan Beberapa Lama Pengeringan - Sri Lestari Hutabarat; Haryati; Irsal Irsal (Talenta Publisher, 2018)
This study aims to determine the effect of osmotic solution on cocoa (Theobroma cacao L.) seed invigoration with several long drying. This research was conducted at the Laboratory of Seed Technology, Faculty of Agriculture, University of Sumatera Utara, from August to September 2016, using a randomized block design with 2 treatment factors. The first factor is a type of solution ie without immersion; equates; coconut water 50%; coconut water 100%; Polyethylene Glycol (PEG) 6000 5%; PEG 6000 10% and the second factor is long drying with 4 levels ie 1 day; 2 days ; 3 days; 4 days. The results showed that the best treatment of osmotic solution was found in the treatment of coconut water with 50% concentration which resulted in a germination rate of 5.51 days and a vigor index of 3.79. The best long of drying treatment was 1 day drying with average germination potential 99.17%, germination rate 4.46 days, normal germination 93.06%, abnormal germination, 12.21%, 5.35% dead seed and vigor index 5,34. The best treatment interaction on the combination of treatment